A NEW NONLINEAR CONSTRUCTIVE METHOD FOR LOSS REDUCTION AND LOAD BALANCING IN RADIAL DISTRIBUTION NETWORK RECONFIGURATION - Baloch, Zahoor Ahmed (European Scientific Journal, ESJ, 2013)
Ineffective utilization of power is one of the reasons of power crisis faced by developing countries. Network reconfiguration is a combinatorial optimization problem to dwindle the power losses by keeping into account the various operational constraints in distribution systems. We propose an improved algorithm to determine the optimal topology among a various alternatives, to reduce the loss reduction and to balance the load. The solution for loss reduction through network reconfiguration involves a guiding search over the relevant configurations, and the load balancing indexes are defined for formulation of objective function of load balancing problem. As a test case this method has been applied on a real network having 20 nodes radial distribution system for loss minimization and load balancing. Our propose system has the advantage that it does not require external parameters, such as barrier factors or crossover rate as contrast to most prevailing systems.